From Diketopiperazines to Hydantoins: An Unprecedented Rearrangement - Chaubet, Guilhem; Cazals, Guillaume; Lebrun, Aurélien; Martinez, Jean; Parrot, Isabelle (Synlett, 2014)
Bis-Boc-activated 2,5-diketopiperazines on reaction with potassium hydroxide or sodium methoxide in dry tetrahydrofuran led to Boc-protected hydantoins through an unprecedented ring contraction. This rearrangement was applied to several monosubstituted 2,5-diketopiperazines with good yields and regioselectivity.
Keywords: ring contraction; rearrangement; heterocycles; lactams; amino acids